Understanding the response heterogeneity of different cancer cell types toward anti-mitotic drugs II – Vinblastine - Xiao, Li Ming (2010)
Vinblastine is a microtubule-destabilizing agent used in cancer chemotherapeutic treatment. It acts by binding to microtubules and promoting the depolymerization of microtubules. As a main component of mitotic spindles, microtubules play an important role in mitosis. The action of vinblastine on microtubules leads to the failure of spindle formation, and hence activating spindle assembly checkpoint. This checkpoint inhibits the cell to exit from mitosis. Prolonged vinblastine treatment is found to trigger apoptosis in these mitotic-arrested cells. However, there are cells which are capable of escaping from this mitotic arrest after prolonged drug treatment. In our investigation, we are interested to understand the response of different cancer cells towards vinblastine. Experiments were carried out on HeLa cells and A549 cells. Upon drug treatment, both HeLa cells and A549 cells underwent mitotic arrest. HeLa mitotic cells accumulated with prolonged drug treatment, but A549 mitotic cells were able to escape from mitosis and continue into interphase. Mitotic slippage due to spindle assembly checkpoint defects has been our initial focus in the experiment. However, protein analysis between the two cell lines has given us other possible explanation of this mitotic slippage.